Exosomes Derived from Apelin-Pretreated Mesenchymal Stem Cells Ameliorate Sepsis-Induced Myocardial Dysfunction by Alleviating Cardiomyocyte Pyroptosis via Delivery of miR-34a-5p - Li T; Zhao Y; Cao Z; Shen Y; Chen J; Huang X; Shao Z; Zeng Y; Chen Q; Yan X; Li X; Zhang Y; et al. (International Journal of Nanomedicine)
Ting Li,1,2,* Yuechu Zhao,3,* Zhi Cao,2,* Ying Shen,2 Jiaqi Chen,2 Xinran Huang,2 Zhuang Shao,2 Yi Zeng,2 Qi Chen,2 Xiaofei Yan,3 Xin Li,1,2 Yuelin Zhang,1,2 Bei Hu1,2 1School of Medicine, South China University of Technology, Guangzhou, Guangdong, People’s Republic of China; 2Department of Emergency Medicine, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 3Guangdong Cardiovascular Institute, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuelin Zhang; Bei Hu, Department of Emergency Medicine, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, Guangdong, 510080, People’s Republic of China, Tel +86-20-83827812-20974, Email zhangyuelin1999@163.com; qhubei@hotmail.comBackground: Exosomes sourced from mesenchymal stem cells (MSC-EXOs) have become a promising therapeutic tool for sepsis-induced myocardial dysfunction (SMD). Our previous study demonstrated that Apelin pretreatment enhanced the therapeutic benefit of MSCs in myocardial infarction by improving their paracrine effects. This study aimed to determine whether EXOs sourced from Apelin-pretreated MSCs (Apelin-MSC-EXOs) would have potent cardioprotective effects against SMD and elucidate the underlying mechanisms.Methods: MSC-EXOs and Apelin-MSC-EXOs were isolated and identified. Mice neonatal cardiomyocytes (NCMs) were treated with MSC-EXOs or Apelin-MSC-EXOs under lipopolysaccharide (LPS) condition in vitro. Cardiomyocyte pyroptosis was determined by TUNEL staining. RNA sequencing was used to identify differentially expressed functional miRNAs between MSC-EXOs and Apelin-MSC-EXOs. MSC-EXOs and Apelin-MSC-EXOs were transplanted into a mouse model of SMD induced by cecal ligation puncture (CLP) via the tail vein. Heart function was evaluated by echocardiography.Results: Compared with MSC-EXOs, Apelin-MSC-EXO transplantation greatly enhanced cardiac function in SMD mice. Both MSC-EXOs and Apelin-MSC-EXOs suppressed cardiomyocyte pyroptosis in vivo and in vitro, with the latter exhibiting superior protective effects. miR-34a-5p effectively mediated Apelin-MSC-EXOs to exert their cardioprotective effects in SMD with high mobility group box-1 (HMGB1) as the potential target. Mechanistically, Apelin-MSC-EXOs delivered miR-34a-5p into injured cardiomyocytes, thereby ameliorating cardiomyocyte pyroptosis via regulation of the HMGB1/AMPK axis. These cardioprotective effects were partially abrogated by downregulation of miR-34a-5p in Apelin-MSC-EXOs.Conclusion: Our study revealed miR-34a-5p as a key component of Apelin-MSC-EXOs that protected against SMD via mediation of the HMGB1/AMPK signaling pathway. Keywords: Exosomes, mesenchymal stem cells, apelin, sepsis-induced myocardial dysfunction, pyroptosis